The Association Between Cardiovascular Disease Risk Factors and Motor Vehicle Crashes Among Professional Truck Drivers. Issue 8 (August 2016) - Ronna, Brenden B.; Thiese, Matthew S.; Ott, Ulrike; Effiong, Atim; Murtaugh, Maureen; Kapellusch, Jay; Garg, Arun; Hegmann, Kurt
Abstract : Objective: This study assesses relationships between the Framingham cardiovascular disease risk (CVD risk) score and prevalence of US Department of Transportation (DOT)-reportable crashes in commercial motor vehicle (CMV) drivers, after controlling for potential confounders. Methods: Data were analyzed from CMV drivers ( N  = 797) in a large cross-sectional study. CVD risk was calculated for each driver. Adjusted odds ratios (ORs) and 95% confidence intervals (95% CIs) between CVD risk and DOT-reportable crashes were calculated. Results: Drivers in the two highest CVD risk groups had significantly higher likelihood of crash (OR = 2.08, 95% CI = 1.20 to 3.63 and OR = 1.99, 95% CI = 1.05 to 3.77, respectively) after adjusting for confounders. There was a significant trend of increasing prevalence of crashes with an increasing CVD risk score ( P  = 0.0298). Conclusion: Drivers with a high CVD risk had a higher likelihood of a crash after controlling for confounders.